The Problem of the Past: Bernard Williams on Ethical Nostalgia - Lukic, Vladimir (My University, 2022)
Contemporary populist rhetoric is often filled with elements that invoke nostalgia. This invocation serves as a powerful tool for affirming the status quo, whilesimultaneously ensuring the efficiency of the rhetoric itself. This paper seeks to provide a critique of the politically induced nostalgia that mediates social opinions, which we shall refer to as the "Golden Age Fallacy" in reference to the famous movie Midnight in Paris. We shall draw from Bernard Williams' work In the Beginning there was the Deed to consider four arguments that form the basis of our criticism: the argument of moral and political regression, temporal desynchronicity, subjective experience, and reactivity. Together, these arguments will provide the foundation for our critique of the Golden Age.
Keywords: Bernard Williams; ethical nostalgia; politics of reactivity; moral regress; Golden Age fallacy; political rhetoric; past; statusquo; sentiment; deliberatio